Online design auction / Beverley Marsha Jokolin Jominit - Beverley Marsha , Jokolin Jominit (2003)
The project that we are developing is called Online Design Auction. It is a website that functions as an online store and marketplace selling banners, animated images, website templet, static logos, animated logos and flash introduction. It provides service solution to customers in order for them to capitalize on the latest multimedia designs quickly and cost-effectively without the burden of building, managing and maintaining a web site. It also allows customers placing bids on images sold online in the catalogue. Developers of this site will be able to display and control catalogue of designs so that buyers can browse through the catalogue and activate orders. With the development of this system, it is divided into two parts which is the Multimedia part that is handled by my partner, Melanie and the other part is the Transaction part which is handles by me. The multimedia part focuses heavily on the searching and browsing of images in the catalogue. The Transaction part focus more on the purchasing actions of images that users want to buy.